Erbium ring fiber laser cavity based on tip modal interferometer and its tunable multi-wavelength response for refractive index and temperature (2018)
A tunable multi-wavelength fiber laser is proposed and demonstrated based on two main elements: an erbium-doped fiber ring cavity and compact intermodal fiber structure. The modal fiber interferometer is fabricated using the cost-effective arc splice technique between conventional single-mode fiber and microfiber. This optical fiber structure acts as a wavelength filter, operated in reflection mode. When the refractive index and temperature variations are applied over the fiber filter, the ring laser cavity provides several quad-wavelength laser spectra. The multi-wavelength spectra are tuned into the C-band with a resolution of 0.05 nm. In addition, the spectra are symmetric with minimal power difference between the lasing modes involved, and the average of the side mode suppression ratio is close to 37 dB. This laser offers low-cost implementation, low wavelength drift, and high power stability, as well as an effect of easy controllability regarding tuned multi-wavelength